Roselyne et les lions - Beineix, Jean-Jacques 1946-2022; Pasco, Isabelle 1966-; Sandoz, Gérald; Clévenot, Philippe; Meisner, Günter (Collection Beineix, 2006)
"A failure at school, Thierry (Gérard Sandoz) does odd jobs at the local zoo in exchange for lessons from the lion tamer Frazier (Gabriel Monnet). He meets another trainee Roselyne (Isabelle Pasco) and they fall in love. Frazier dismisses Thierry for disobedience and Roselyne leaves with him. With the help of Thierry's English teacher Bracquard (Philippe Clevenot) they travel across France looking for work. They join a circus but are not allowed to work with the lions. Finally they join Koenig's circus in Munich. Roselyne is employed as the performer with Thierry as the trainer. Here they meet the tiger trainer Klint (Gunter Meisner)." -- IMDB.